(untitled) (Fiep Bulletin - online, 2017)
The aim of the study was to verify the return curve of lactate to baseline levels after a session of the Tabata protocolwith a stationary bike roller. Therefore Ten male cyclists (30.95 ±6.46 years, 80.07 ±9.04 kg; 177.1 ±6.84 cm) were submitted toeight maximum intensity of 20s series, 10s active recovery there between. Venous blood collected the day before the test,pretest, posttest, after 1h, 12h, 24h, 48h, and 72h characterized the study design. There was a significant difference (p<0.05) inthe post-test collections and after 1h, returning to baseline levels in post collection 12h. The peak of the curve was the post-test.The Tabata protocol causes changes in blood lactate concentrations, and normalcy turns between 1h and 12h after exercise.